Peningkatan Pengetahuan Penggunaan Gadget pada Pelajar dalam Menyikapi Perkembangan Game yang Mengakibatkan Ketergantungan Bagi Penggunanya - Argiyan Dwi Pritama; Gustin Setyaningsih; Muhammad Ikhsan Maulana; Rafi Rahmat Dani; Muhamad Awiet Wiedanto Prasetyo; Toni Anwar (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Where advances in digital science and technology make various demands for creativity and innovation must always be developed, as is done by teachers and teaching staff at SD Al Irsyad Islamiyyah 02 Purwokerto. The essence of education is the teaching and learning process. The better the teaching and learning process is implemented, the better the quality of education will be. The problem experienced by SD Al Irsyad Islamiyyah 02 Purwokerto is that students often play with gadgets without clear directions for their use and are not monitored properly. In this service activity, the team socializes the use of gadgets among students in response to the development of games which result in dependency for their users. It is hoped that students will have the awareness to reduce their use of gadgets or at least be able to make good use of them through applications and games that have educational value. Flow of program implementation from Preparation Stage, Socialization Stage, Evaluation Stage and Mentoring Stage. The conclusion of this program is an increase in students' understanding of using gadgets wisely from 60% to 90%, with an increase in student participation from 30% to 80%. The follow-up to this activity includes further mentoring sessions and integration of learning with the use of gadgets by teachers.